Historical relativism and the essence of Christianity. (2nd January 2016) - Kaufman, John
Abstract : This article is a series of reflections by a historian who is also a theologian on some of the theological challenges raised by historicism and the historical study of Christianity. In particular, the question is raised as to whether it is still meaningful to speak of Christianity as having some form of normative "core" given at some point in the past, or an unchanging normative "essence" by which all forms of Christianity can be evaluated. The article begins with a brief look at Adolf von Harnack's lectures on the essence of Christianity from 1900, before moving into reflections on historical change, relativity and normativity. The author rejects the idea of a religion having an unchanging normative core or essence. Like any other human institution, Christianity has been continually changing and adapting to new contexts, even though its representatives might claim an unchanging continuity. The article concludes with some reflections on the possible contours of a modest theology informed by these historicist reflections.